PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI BERBASIS MICROSOFT ACCESS PADA TOKO CHANDRA JAYA MESIN - Nurlita Kara Tarigan; Sarikadarwati; Selvita Meilan Sari; Anggeraini Oktarida; Dian Ofasari Dian (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2026)
This report is titled “Design of a Microsoft Access-Based Cash Sales Accounting Information System at Toko Chandra Jaya Mesin.” Toko Chandra Jaya Mesin is a trading business engaged in selling technical equipment and machinery. The purpose of this report is to develop a computerized cash sales accounting information system application. Primary data were collected through interviews with the owner and employees regarding the current cash sales recording procedures. The existing manual system has several weaknesses, such as inefficient transaction recording as the number of customers increases, difficulties in identifying products with increasing or decreasing sales trends, obstacles in quickly compiling sales summaries, and a higher risk of data loss due to the absence of backups. The author concludes that the design of the cash sales accounting information system application for Toko Chandra Jaya Mesin using Microsoft Access was carried out through stages of computerized system planning analysis, application design, and application testing, resulting in sales report outputs.